Analysing Tourism Expenses using Mathematical Modelling - Janzakov Bekzot Kulmamat ugli; Sultonov Beknazar; Umirov Islombek; Utkirov Aslbek; Tursunboyev Madamin (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
The article considers the ways a potential tourist would spend his/ her funds in three-day tour package in Samarkand city. For this purpose, a mathematical simulation model based on Monte Carlo method was used. As a result of the analysis, it was found that the total expenses of tourists were greatly influenced by the costs of transport and food.